Healthcare for Trans*gender People in Germany: Gaps, Challenges, and Perspectives - Guethlein, Nora; Grahlow, Melina; Lewis, Carolin A.; Bork, Stephan; Habel, Ute; Derntl, Birgit (Frontiers in Neuroscience, 2021)
People whose gender does not correspond to the binary gender system, i.e. trans*gender people, face two main problems when it comes to health care in Germany: (1) They often suffer from general psychiatric comorbidities as well as specific and significant mental distress due to gender dysphoria, and (2) the German healthcare system lacks sufficiently educated and clinically experienced medical personnel who are able to provide specialized health care. Aside from transition, it often is extremely difficult for trans*gender people to get access to and integration into the medical system. Stigmatization and pathologization in treatment are widespread; as are long waiting times for specialized health care providers who are often only accessible to those trans*gender people willing to travel long distances. Frequently, trans*gender people face further difficulties and barriers after transition, as some health care professionals fail to provide nuanced care (e.g., gynaecological consultation for transmen). The ICD-11 German Modification (ICD-11-GM), which should be routinely used by 2022, implements a depathologization of trans*gender people in the medical system. This paper compares the issues related to health and health care of trans*gender people in Germany with those in other European countries. We review the offered care by specialized centers with regard to treatment of and support for trans*gender people. We conclude with specific proposals that may contribute to establish an improved, up-to-date, gender-sensitive healthcare system.